Adsorption of o-Cresol from Its Aqueous Solution on Granular Activated Carbon Columns - Singh, Shripal; Yenkie, M.K.N. (Asian Journal of Chemistry, 2010)
Compliance with stringent discharge limits and the most economic way of achieving it without loss of production has led to continued refinement of existing treatment technologies and the recognition and development of promising emergent technologies. Adsorption on granular activated carbon (GAC) has proved itself as an efficient technology for removal of final traces of a broad spectrum of toxic organic compounds from domestic and industrial wastewaters. In the present investigation, experiments have been carried out to determine the effect of various physico'-chemical parameters associated with both adsorbent and adsorbate on the adsorption of o-ctesol from aqueous phase. Some design parameters such as bed height,. adsorbate flow rate, temperature, initial adsorbate concentration and adsorbate pH for efficient designing of fixed bed GAC columns has also been investigated. The commercially available bituminous coal based granular activated carbon Filtrasorb-300 (F 300) was used as adsorbent. The validity of the Michael's mass tranfer zone (MTZ) concept for designing adsorption columns was used in this work.